2007
DOI: 10.1128/iai.00393-07
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor A Dampens Induction of Inflammation in Response to the Fungal PathogenPneumocystis carinii

Abstract: Alveolar macrophages are the effector cells largely responsible for clearance of Pneumocystis carinii from the lungs. Binding of organisms to ␤-glucan and mannose receptors has been shown to stimulate phagocytosis of the organisms. To further define the mechanisms used by alveolar macrophages for clearance of P. carinii, mice deficient in the expression of scavenger receptor A (SRA) were infected with P. carinii, and clearance of organisms was monitored over time. SRA-deficient (SRAKO) mice consistently cleare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…For example, it has been shown that scavenger receptor A family members negatively regulate immune activity triggered by tumors, fungal pathogens, and apoptotic cells (11,42,43). In our studies, we have shown that dual engagement of SR-B1 and TLR9 by CpG negatively regulates the production of pro-inflammatory mediators such as IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 49%
“…For example, it has been shown that scavenger receptor A family members negatively regulate immune activity triggered by tumors, fungal pathogens, and apoptotic cells (11,42,43). In our studies, we have shown that dual engagement of SR-B1 and TLR9 by CpG negatively regulates the production of pro-inflammatory mediators such as IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 49%
“…For example, SR-A can recognize several pathogen-associated molecular patterns, such as lipopolysaccharide, lipoteichoic acid, bacterial CpG DNA, double-stranded RNA, and yeast zymosan/b-glucans (Zhu et al, 2001;Mukhopadhyay and Gordon, 2004;Hollifield et al, 2007;Limmon et al, 2008;Areschoug and Gordon, 2008). The contribution of the innate immune and inflammatory responses to cerebral I/R has been well demonstrated (Jordan et al, 2008;Brea et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Scavenger receptor A has recently been shown to act as a PRR and has an important role in the induction of innate immune and inflammatory responses (Zhu et al, 2001;Hollifield et al, 2007;Limmon et al, 2008). For example, SR-A can recognize several pathogen-associated molecular patterns, such as lipopolysaccharide, lipoteichoic acid, bacterial CpG DNA, double-stranded RNA, and yeast zymosan/b-glucans (Zhu et al, 2001;Mukhopadhyay and Gordon, 2004;Hollifield et al, 2007;Limmon et al, 2008;Areschoug and Gordon, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations